(untitled) (International Journal of Engineering and Computer Science, 2017)
Traffic management on the road has become a severe problem of today’s society because of growth of the urbanization. This leads to traffic jam at the traffic junctions which in turn causes delay to ambulances. In order to overcome this problem, this paper presents a simple ambulance controlled traffic system. The main objective of this system is that to control the traffic, allowing an ambulance to arrive at a particular location without it having to stop anywhere until the destination is reached. This system includes RFID technology and LabVIEW software. An RFID reader reads the ID number from the corresponding ambulance RFID tag and then it is sent to microcontroller LPC 1768H, which is programmed, with the help of embedded C instructions. This microcontroller is capable of communicating with input and output modules. The RFID readers provide the information to the microcontroller so that it compares the received ID with default ID’s stored in its memory. If the obtained ID gets matched with any of the ID’s , then a green signal is given along the path of the ambulance or else no change in the signal takes place. The signal won’t change from green color until the same tag is detected by the other reader in another route. If the tag is detected in other route, then a normal traffic signal operation is performed. This system includes the simulation observation. The operation which is performed on hardware circuit is similarly observed on front panel of the LabVIEW. Moreover, the designed system has simple architecture, fast response time, ease in understanding the working module, user friendliness and scope for further expansion